TRANSFORMING ORGANIZATIONAL CULTURE IN IMPROVING THE PERFORMANCE OF EMPLOYEES OF PT. PEGADAIAN (PERSERO) AT REGIONAL OFFICE VII DENPASAR - Intan Mandasari; Ida Ayu Putu Sri Widnyani; Riant Nugroho (DIA: Jurnal Administrasi Publik, 2021)
The research results in 1. Organizational culture transformation that occurred seen from background for transformation is driven by extraordinary technological developments, this situation initiated the creation of a new business model that requires financial service products to be more efficient, fast, easy, and customer-friendly; the process and form of transformation includes business and the operational transformation that focuses on the customer and the HR transformation and the form of digital transformation; Standard provisions and SOPs; socialization, the process of transforming organizational culture should be communicated and assured by the leader to all employees as clearly as possible; the facilities and infrastructure owned in general are quite adequate, but for the need for digital transformation, these facilities and infrastructure still needs to be revitalized and modernized; the condition of human resources still have to be improved for the competence; and the impact or the outcome of the transformation of organizational culture cannot be said to improve employee performance; 2. The constraints on transforming organizational culture to improve employee performance include constraints due to communication, infrastructure, and HR; and 3. The solutions to overcome the obstacles to the ongoing transformation of organizational culture. The method used in this research is descriptive qualitative.